2021
DOI: 10.3390/su13052912
|View full text |Cite
|
Sign up to set email alerts
|

COVIDTAS COVID-19 Tracing App Scale—An Evaluation Framework

Abstract: Mobile apps play an important role in COVID-19 tracing and tracking, with different countries taking different approaches. Our study focuses on 17 government owned COVID-19 Contact Tracing Apps (CTAs) and analyze them using a proposed COVIDTAS framework. User satisfaction is not directly related to the COVIDTAS score or the interaction between users and the app developers. To increase adoption of CTAs, government leadership must offer assurance to its citizens that their identify will be concealed and emphasiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…Several studies suggest that the symptoms associated with COVID-19 may be exacerbated due to increasing pollution levels [57], a fact that closely connects SDGs 3 (on health) and 11 (on sustainable cities). Another important aspect regarding the management of the COVID-19 has to do with the digital-contact-tracing apps, which aimed at achieving better control of the pandemic, with a positive impact on SDG 3, but could potentially exhibit challenges [58][59][60] in the context of SDGs 10 (on reduced inequalities) and 16 (on strong institutions). The connections reported above have a clear relation with the results presented in Table 9, where the number of Indian COVID-19 articles and their citations related to each of the 17 SDGs are reported.…”
Section: Covid-19 Studies Connected To Sustainable Developmentmentioning
confidence: 99%
“…Several studies suggest that the symptoms associated with COVID-19 may be exacerbated due to increasing pollution levels [57], a fact that closely connects SDGs 3 (on health) and 11 (on sustainable cities). Another important aspect regarding the management of the COVID-19 has to do with the digital-contact-tracing apps, which aimed at achieving better control of the pandemic, with a positive impact on SDG 3, but could potentially exhibit challenges [58][59][60] in the context of SDGs 10 (on reduced inequalities) and 16 (on strong institutions). The connections reported above have a clear relation with the results presented in Table 9, where the number of Indian COVID-19 articles and their citations related to each of the 17 SDGs are reported.…”
Section: Covid-19 Studies Connected To Sustainable Developmentmentioning
confidence: 99%
“…In supporting the effort in mitigating disease transmission from the coronavirus pandemic (Covid-19), the cloud, cell-networks and IoT devices such as smart-phones, sensors and domestic appliances, continue to play a vital role in a wide range of global Tracing-Testing-Tracking programs. Many different approaches are adopted by global communities in minimising person-to-person transmission [ 21 , 22 ]. This demonstrates that in response to the pandemic, coupled with the urgency in developing and deploying digital solutions, data privacy implications become ever more challenging with increasing data privacy risks.…”
Section: Data Privacymentioning
confidence: 99%
“…In a Republic of Ireland survey conducted with over 8000 participants, it was found that 54% would accept using a contact tracing app. Similarly, in the UK from a survey of 2000 participants found that 55% would accept using a government-controlled app, with higher uptake specifically for the NHS contact tracing app [ 21 ]. This information demonstrates a lack of app uptake in the remaining 45% of the British population that could undermine a governments ability in effectively handling data collection and the processing of critical medical information.…”
Section: Data Privacymentioning
confidence: 99%
See 1 more Smart Citation
“…It has occurred at a time when the flow of digital transformation, which seeks to fundamentally change the competitive model of the global industry, was in full swing. Digital technology has been usefully used to solve human crises in various fields [1]. In addition, as strong social distancing was implemented after the COVID-19 pandemic, the demand for non-face-to-face work using new technologies, regardless of public and private sectors, has increased.…”
Section: Introductionmentioning
confidence: 99%